2020
DOI: 10.1016/j.ccell.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Transcriptomic Characterization of Natural Killer T Cell Lymphoma

Abstract: Highlights d Integrated analysis provides insight into the molecular classification in NKTCL d EBV lytic genes play an important role on NKTCL pathogenesis d Genomic alteration-based molecular subtypes associate with clinical outcomes d MYC, histone acetylation, and PD-L1/2 are potential therapeutic targets of NKTCL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
222
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(265 citation statements)
references
References 88 publications
9
222
2
1
Order By: Relevance
“…Mutations in ARID1A, KMT2D, TET2, and BCORL1 for case 9 suggested deregulation of the epigenetic control of transcription. This patient seemed to belong to the HEA subtype 28 and was more sensitive to the histone deacetylase inhibitors. ARID1A is a tumor suppressor gene and several studies showed that ARID1A mutations were associated with Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mutations in ARID1A, KMT2D, TET2, and BCORL1 for case 9 suggested deregulation of the epigenetic control of transcription. This patient seemed to belong to the HEA subtype 28 and was more sensitive to the histone deacetylase inhibitors. ARID1A is a tumor suppressor gene and several studies showed that ARID1A mutations were associated with Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The third patient with poor clinical outcome (case 9) exhibited mutations mainly at the epigenetic modifiers, as previously defined. 28 Gene Ontology-Biological Process (GO-BP) enrichment analysis revealed that the T-cell receptor signaling pathway, immune response-regulating pathway, and immune response-activating pathway were enriched in the group without disease progression (cases 3, 4, 5, and 6) ( Supplementary Fig. 4).…”
Section: Patientsmentioning
confidence: 99%
“…Natural killer/T-cell lymphomas (NKTCL) are invariably infected with EBV, and EBV-infected lymphoma cells upregulate PD-L1 expression [ 37 ]. Recent data have also revealed distinct molecular subtypes of NKTCL, one of which is of clinical relevance and associates to a subtype with alterations of the immune modulator JAK-STAT mutations/amplification of the 9p24.1/PD-L1/2 locus [ 136 ]. Adult T-cell leukemia/lymphoma (ATLL), an aggressive T-cell malignancy caused by human T-cell leukemia virus type 1 (HTLV-1) [ 137 ], carries a high mutational burden of genes, including the T-cell receptor, NF- κ B, and immune surveillance mechanisms [ 138 ].…”
Section: Peripheral T Cell Lymphomas (Ptcl)mentioning
confidence: 99%
“…In addition, JAK3, STAT3, and STAT5B mutations leading to the constitutive activation of the JAK/STAT pathway have been reported in ENKTL [75][76][77][78][79]. Xiong et al [80] also demonstrated presence of JAK2, JAK3, STAT3, STAT5A, and STAT5B mutations/ amplifications although their mutational frequency varies between different studies and ranges from 0 to 35% [67]. Other factors such as inactivation of PTPRK by gene deletion and aberrant promoter hypermethylation also results in constitutive activation of JAK/STAT pathway [81], suggesting the diverse molecular mechanisms underlying the activation of JAK/STAT pathway.…”
Section: Extranodal Nk/t Cell Lymphoma Nasal Typementioning
confidence: 99%
“…More recently, integrated analysis of the genomic and transcriptomic features has been used to define three molecular subtypes of NK/T cell lymphoma, termed TSIM, MB, and HEA subtype [80]. TSIM NK/T cell lymphoma seem to arise from NK cells, whereas MB and HEA subtypes may arise from T cells.…”
Section: Extranodal Nk/t Cell Lymphoma Nasal Typementioning
confidence: 99%